Update on clinical and experimental management of diabetic cardiomyopathy: addressing current and future therapy - Galis, Peter; Bartosova, Linda; Farkasova, Veronika; Bartekova, Monika; Ferenczyova, Kristina; Rajtik, Tomas (Frontiers in Endocrinology, 2024)
Diabetic cardiomyopathy (DCM) is a severe secondary complication of type 2 diabetes mellitus (T2DM) that is diagnosed as a heart disease occurring in the absence of any previous cardiovascular pathology in diabetic patients. Although it is still lacking an exact definition as it combines aspects of both pathologies – T2DM and heart failure, more evidence comes forward that declares DCM as one complex disease that should be treated separately. It is the ambiguous pathological phenotype, symptoms or biomarkers that makes DCM hard to diagnose and screen for its early onset. This re-view provides an updated look on the novel advances in DCM diagnosis and treatment in the experimental and clinical settings. Management of patients with DCM proposes a challenge by itself and we aim to help navigate and advice clinicians with early screening and pharmacotherapy of DCM.